Development of a Social Communication Questionnaire (QSC-ID) for People With Intellectual Disability in a Deaf Sample: A Pilot and Feasibility Study - Weber, Chantal; Weber, Christoph; Fellinger, Johannes; Holzinger, Daniel (Frontiers in Psychiatry, 2021)
Background: Social communication (SC) includes the use and interpretation of verbal and non-verbal messages within a social context and thus requires more than knowledge of language. Social communication skills are essential for connecting and engaging with others, and SC deficits are often associated with emotional and behavioral problems. There is a lack of feasible instruments for assessing SC skills in individuals with intellectual disability (ID). Methods: A questionnaire on social communication in adults with ID (QSC-ID) comprising 20 Likert-scaled items was developed and completed on behalf of participants (n = 52) from three Austrian therapeutic living communities for people with ID and deafness by their living- and working-facility key caregivers. The sample of adults with hearing loss was considered ideal for the development of a measure of SC that is not restricted to a specific communication mode or overly related with language skills. Results: The preliminary results showed high construct validity. Correlations were high between SC and language, social skills, and severity of autism spectrum disorder (ASD), moderate between SC and adaptive skills, and non-verbal intelligence and, as expected, low between SC and motor skills. Interrater reliability was found to be good or at least acceptable for all items. Total raw scores were well-distributed over the whole range—Cut-offs based on the 10th and 20th percentile are suggested to identify atypical and borderline SC skills. Caregiver feedback and completeness of data suggest that the questionnaire is highly feasible. Conclusion: Questionnaire on social communication in adults with ID is an easy-to-use caregiver-reported questionnaire for use with individuals with mild to severe forms of ID. Initial testing of validity looks promising. Further validation in populations with typical hearing is required. Due to substantial correlations between SC and structural language skills the calculation of specific SC cut-offs for different levels of linguistic skills should be considered when sufficient data is available.